An Analytical Study on Determinants of Capital Structure Composition During the Post Liberalization Period in India - Batra, Geetika; Munjal, Alka (Indian Journal of Finance, 2018)
This paper analyzed the capital structure composition of firms during the post financial liberalization period in India. The study used data of 41 Indian listed firms excluding financial services firms listed on Nifty indices on National Stock Exchange over a time frame of 14 years. The dependent variables taken for financial leverage were EBITDA to interest expense, equity to total assets, and long - term debt to total assets. The capital structure composition was studied across various dimensions, that is, profitability, tangibility, growth, size, volatility, ownership pattern, etc. along with other external dimensions such as taxation policy. Data analysis was done using descriptive statistics, correlation, and stepwise regression analysis. Three different models were constructed for analysis through stepwise multiple regression to deduce a unique set of explanatory variables that affected the leverage measure of firms. These models helped to analyze the maximum number of significant factors that had an impact upon the capital structure composition during the post liberalization period in India. The findings of this study suggested that all the explanatory variables studied in the three models were statistically significant with leverage. The results showed that there was an impact of financial liberalization on capital structure composition. ln(EBITDA to interest expense) explained the maximum variation in the capital structure composition after liberalization followed by ln(equity to total assets).